Boys Do Cry: a randomised controlled trial testing the effects of a music video promoting help-seeking for mental health difficulties in Australian men - Angela Nicholas; Simone Scotti Requena; Simon Rice; Matthew J. Spittal; Andrew MacKinnon; Zac Seidler; Maria Ftanou; Justine Fletcher; Long Le; Cathy Mihalopoulos; Jane Pirkis (BMC Public Health, 2025)
Abstract Background In Australia and internationally, it is men who predominately die by suicide. Men are less likely than women to seek help for their mental health difficulties and this may contribute to their higher suicide rates. We created a 4-minute music video encouraging Australian men to seek help for mental health difficulties (Boys Do Cry). We aimed to assess in a randomised controlled trial (RCT) whether the Boys Do Cry video increased men’s intentions to seek help for mental health difficulties from baseline (T1) to post-intervention (1 week = T2). Methods We conducted an online single-blind, two-arm RCT comparing the effects of Boys Do Cry against a control video. Analyses were undertaken on an intent-to-treat basis using linear mixed effects models with variables for trial arm, occasion of measurement and their interaction. Intervention effectiveness was assessed by comparing the mean difference between arms in change of the total score on the General Help-Seeking Questionnaire (GHSQ) from T1 to T2. Results 476 participants were randomised (intervention = 243; control = 233). At T1, GHSQ means were similar (intervention = 45.28; control = 45.70). After viewing the videos, GHSQ means increased in both arms (intervention = 47.33; control = 46.59), with no evidence of a difference in scores at T2 (modelled mean difference = 0.62, 95% CI -1.11 to 2.35, p = 0.485). Similar results were observed for all secondary outcomes. No adverse events were observed. Conclusions Boys Do Cry demonstrated some evidence of a positive effect on help-seeking intentions among Australian men; however, so too did the control video, and no significant difference was observed. Trial registration ANZCTR No. 2,621,001,008,819. Registered 30 July 2021.